(untitled) (Bangladesh Journal of Medical Science, 2023)
Aim: The specific aim of the study was to assess the impact of COVID-19 pandemic on nursing faculty experiences. Background: Academic nursing experiences were disrupted due to the COVID-19 pandemic. There is concern that the resulting stress threatens nursing faculty emotional well-being and reason to burnout. Method: A descriptive, quantitative study was conducted; exploring faculty academic and clinical roles during the COVID-19 pandemic by using structured, self designed, open-ended questionnaire to 401 institutionally attached nursing health professionals. The questionnaire includes various domains including Safety and Health, Challenges for teaching, clinical practise, supervision perception of institutional support provided; faculty burnout, satisfaction, and well-being. Results: Overall satisfaction with the working environment in the institutions with respect to total teaching experience showed a significant statistical. Participants perceived support from academic institutions and increased need to provide emotional support to students. Conclusion: Nursing faculty are essential to the profession. Nursing faculty require proactive and sustained institutional and personal support to provide exceptional ongoing education, build resilience, and support students. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.148-156